Assessment of learning preferences among medical students - Krishnan, Malavika; P. Sawant Dessai, Bhargav; K. Shah, Hemangini (International Journal Of Community Medicine And Public Health, 2023)
Background: Facilitating learning, or the development of knowledge, skills, attitudes, beliefs, and habits, is what education is all about. The learning style of an individual refers to how they prefer to gather, process, memorize, and recall information. One student may adopt one or many modes of knowledge acquisition. Academics consider learning style as a factor influencing students’ learning as a result of personal preferences for physical, social, and environmental components during the learning process. Methods: The cross-sectional study was conducted from July to September 2022, at Goa Medical College. The student’s preferred method of learning was ascertained using the VARK questionnaire which consisted of 16 questions in the VARK questionnaire. Each question offers 4 options, which correlate to the preferences for the 4 sensory modalities. The students were told to select the response that best reflected their preferences. Results: A total of 867 medical students completed the questionnaire. Among the students 368 (41%) preferred unimodal learning style (either visual, auditory, reading/writing, or kinesthetic), 173 (20%) preferred usage of bimodal learning style, 126 (15.8%) trimodal and 200 (23.2%) quadrimodal learning style. Conclusions: There is a variety of learning styles present in the classroom, and there are some students who are not addressed by the standard lecture format. Furthermore, this study demonstrated that students prefer multimodal methods. It is the responsibility of the instructor and the student to be aware of student learning style preferences to improve learning. As instructors, we need to assess and understand how to reach all students by understanding how to present information in multiple modes.